Analytical solutions of certain homogeneous integral equations - Mirolyubov, A. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:А. А. Миролюбов. Аналитические решения некоторых однородных интегральных уравненийA. Miroliubovas. Kai kurių homogeninių integralinių lygčių analiziniai sprendiniai